Creative geographies of ceramic artists: knowledges and experiences of landscape, practices of art and skill. (17th February 2017) - Miller, Alex
Abstract: This paper argues for a conception of art as an embodied and creative material practice. It draws on research conducted with seven professional ceramic artists who deal with landscape in their work to explore their processes of art-making through interview and (filmed) observation. It demonstrates the distributed range of embodied and relational more-than-artistic practices which inform how landscape is encountered, known and ultimately represented. It argues that artists' self-expression in art is based upon material, social and political knowledges which interweave in artists' lives. By studying ceramicists' making this paper demonstrates both the non-conscious skill and the conscious technical knowledge needed to make art. It shows chance to have a triple role in practices of making, as something to work alongside, to work against and to draw on as a creative resource. This paper both argues for and demonstrates the value of an approach to art-making that frames it as a complex of both conscious, socio-cultural, technical knowledges and non-conscious skills which together (in)form works of (ceramic) art.